Nigeria-Israeli Relations: “So Fragile So Emotional” - Obi-Ani, Ngozika Anthonia; Obi-Ani , Paul (South Asian Journal of Social Sciences and Humanities, 2020)
Israel is technologically advanced and as a result of it, Nigeria after independence in 1960 had developed ties with the State of Israel particularly in areas of agricultural and technical know how. Unfortunately, the Middle East crisis has made the relationship to be rocky at times due to Nigerians’ religious differences. The predominantly Northern Muslims often reacted adversely towards the Jews due to the Palestinian question while the Southern dominated Christians do not see anything wrong with the Jewish seizure of Palestinian lands in West Bank and Gaza. The break-up of diplomatic ties after the Yom Kipurr War of 1973 by the Oragnisation of African Unity (OAU) was perceived by the Christians in Nigeria as an undue Muslim overreach. This theoretically based research paper used both secondary sources, newspapers and internet materials, to interrogate Nigeria-Israeli relations. The paper concludes that no human relations is sustained on emotions and religious sentiments. Nigerian-Israeli relations has come of age and it should be based on mutual beneficial opportunities for the good of both countries. On the other hand, Nigeria stands to gain from Israeli’s military, technical and agricultural advancement if she becomes more adroit and less emotional in her relations with Israel.